The effectiveness of the use of plastic wrapping on dental unit work desks on the number of bacterial colonies in Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, University of North Sumatra (USU) - Olivia A. Hanafiah; Indra B. Siregar; Abdullah Oes; Elsa M. Sirait (Journal of Dentomaxillofacial Science, 2020)
Objective: The purpose of this research was to determine the effectiveness of the use of plastic wrapping on dental unit work desks on the number of bacterial colonies in Department of Oral and Maxillofacial Surgery Faculty of Dentistry USU.Material and Methods: In this study, sampling was carried out on tooth extraction patients in the Oral and Maxillofacial Surgery Department by using 2 dental chair units where one of the dental unit work desks used plastic wrap and the other did not. Then examination of the number of bacterial colonies was carried out in Microbiology Laboratory, Faculty of Mathematics and Natural Science USU.Results: Samples taken as many as 50 samples (25 pre-test samples and 25 post-test samples) in 5 different days showed a significant difference in the number of bacterial colonies (p<0.05).Conclusion: This study showed that there was a significant decrease in the number of bacterial colonies in the dental unit work desks that used plastic wrap compared to those that do not.